2022
DOI: 10.1007/s40843-021-1932-y
|View full text |Cite
|
Sign up to set email alerts
|

Large reversible upconversion luminescence modification and 3D optical information storage in femtosecond laser irradiation-subjected photochromic glass

Abstract: Fast response, high luminescence contrast, three-dimensional (3D) storage, and nondestructive reading are key factors for the optical storage application of photochromic materials. Femtosecond (fs) laser direct writing technology with multiphoton nonlinear absorption is becoming a useful tool for microprocessing functional units in the 3D space of glass owing to its remarkable advantages, such as a fast processing speed and high processing accuracy. Herein, the photochromism of transparent glass codoped with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…However, the optical information recorded on opaque ceramics or films is two-dimensional (2D) PC storage. To meet the requirement of high-capacity and high-quality optical storage or imaging, three-dimension (3D) PC storage media integrating space and luminescence into a single entity have aroused wide concern, such as glasses and transparent ceramics. , Among them, rare-earth ion doped ferroelectric transparent ceramics, especially (K 0.5 Na 0.5 )NbO 3 (KNN) based ones, are suitable candidates for 3D PC storage, but their low coloration contrast and long response time limit their practical applications. , For instance, the PL intensity modulation in Sm-doped KNN transparent is only 49% after being irradiated by a UV lamp for 5 min . Therefore, new PC transparent ceramics with a fast response time and high coloration contrast are especially attractive for high-quality real-time optical storage and imaging applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the optical information recorded on opaque ceramics or films is two-dimensional (2D) PC storage. To meet the requirement of high-capacity and high-quality optical storage or imaging, three-dimension (3D) PC storage media integrating space and luminescence into a single entity have aroused wide concern, such as glasses and transparent ceramics. , Among them, rare-earth ion doped ferroelectric transparent ceramics, especially (K 0.5 Na 0.5 )NbO 3 (KNN) based ones, are suitable candidates for 3D PC storage, but their low coloration contrast and long response time limit their practical applications. , For instance, the PL intensity modulation in Sm-doped KNN transparent is only 49% after being irradiated by a UV lamp for 5 min . Therefore, new PC transparent ceramics with a fast response time and high coloration contrast are especially attractive for high-quality real-time optical storage and imaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the requirement of high-capacity and high-quality optical storage or imaging, three-dimension (3D) PC storage media integrating space and luminescence into a single entity have aroused wide concern, such as glasses and transparent ceramics. 13,14 Among them, rare-earth ion doped ferroelectric transparent ceramics, especially (K 0.5 Na 0.5 )-NbO 3 (KNN) based ones, 15−19 are suitable candidates for 3D PC storage, but their low coloration contrast and long response time limit their practical applications. 9,20−22 For instance, the PL intensity modulation in Sm-doped KNN transparent is only 49% after being irradiated by a UV lamp for 5 min.…”
Section: Introductionmentioning
confidence: 99%
“…13 For example, Xiao et al reported a transparent glass co-doped with both rare-earth ions and tungsten ions. 14 They used a femtosecond laser to convert W 6+ into W 5+ , whereby a photochromic modulation of upconversion luminescence was achieved. Hu et al reported a transparent phosphate glass doped with Eu 3+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…These exciting potentials attracted us to explore photochromic glasses with luminescence modification as alternative optical storage media. Recently, a rare-earth-ion-doped photochromic tungsten phosphate glass was studied, which exhibits an information encryption and 3D optical storage capacity based on the reversible valence state transformation from W 6+ to W 5+ . , However, a thermal treatment was used to bleach the photochromic tungsten phosphate glass, limiting the practical applications. Thus, an entirely photostimulation induced reversible photochromic glass is particularly attractive for the realization of 3D optical storage applications.…”
mentioning
confidence: 99%